2020
DOI: 10.21315/jps2020.31.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Flame-retardant properties of particleboard made from coconut fibre using modified potato starch as a binder

Abstract: This study seeks to evaluate the flame-retardant characteristics of experimental particleboard manufactured from coconut fibre using modified potato starch as a green binder. The coconut fibre was used as a replacement for the wood as a raw material in particleboard production. The adhesives used in the process were made by modifying potato starch with citric acid and glutardialdehyde. No flame-retardant additive was added during the processing, and this was done to evaluate the flame-retardant potential of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The LOI values obtained in the tests ranged from 29.3-31.3%, indicating good re-retardant properties, mainly in uenced by the coconut ber content(Owodunni et al 2020). Research provided byGürü et al (2015) regarding the use of rice husks and straw in the production of particleboards showed that adding these wastes increases the re resistance of the board.…”
mentioning
confidence: 92%
“…The LOI values obtained in the tests ranged from 29.3-31.3%, indicating good re-retardant properties, mainly in uenced by the coconut ber content(Owodunni et al 2020). Research provided byGürü et al (2015) regarding the use of rice husks and straw in the production of particleboards showed that adding these wastes increases the re resistance of the board.…”
mentioning
confidence: 92%
“…particularly linoleic acid, as a result, natural plant compounds, particularly those from medicinal plants, can be studied in an effort to discover potential alternatives to the various antimicrobials. Numerous phytochemicals found in plants have significant therapeutic benefits that can be employed to cure diseases [3] . Natural and modern antibiotics have eradicated a variety of illnesses, but Pathogens have evolved as a result of their indiscriminate use [4] .…”
Section: Introductionmentioning
confidence: 99%
“… 34 More recently, Owodunni et al reported the use of starch as a binder to manufacture particleboard from coconut fibers and obtained enhanced fire-retardant properties. 35 However, despite all these efforts, scientists studying such starch-based materials are still anticipating the full emergence of these materials as fire-retardant ingredients due to intrinsic deficiencies such as facile hydrolysis and the material's neutral (nonionic) nature.…”
Section: Introductionmentioning
confidence: 99%